EFEKTIVITAS PENDEKATAN MASTERY LEARNING TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA STAIN GAJAH PUTIH TAKENGON - Rahmadhani, Elfi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This article was aimed at viewing the effectiveness of Mastery Learning approach with an understanding of concepts and problem-solving abilities of students at STAIN Gajah Putih Takengon.The samples were students of Islamic Education Studies Program (PAI) of the third semester taking the Basic Statistics Academic Year 2017/2018. The instruments of this research were observation sheet, test and questionnaires. Observation sheet was giving to lecturer and students, tests were giving to students to see understanding of concepts and problem-solving abilities,and questionnaires were giving to students to see student responses in learning by using Mastery Learning approach. Based on the results of this study it can be concluded that Mastery Learning approach is effective to see the understanding of concept and problem-solving ability of students PAI STAIN Gajah Putih Takengon. From the calculation of hypothesis obtained t-count was 2.67 for understanding the concept and t-count was 13.86 for ability to build the problem with t_table was 2.01 and degree of freedom was n -2, or degree of freedom was 41 - 2 = 39, so tcount > ttable, then Ha was accepted.